FAKTOR KEBUDAYAAN, KELAS SOSIAL, SIKAP, KEPRIBADIAN DAN PERSEPSI YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN KAIN SASIRANGAN DI KOTAMADYA BANJARMASIN - Rusman Irwansyah; Nuril Huda; Ahmad Rifani (JWM (JURNAL WAWASAN MANAJEMEN), 2014)
This research aimed to identify and analyze the influence of cultural factors (X1), social class (X2), attitude (X3), personality (X4), and perception (X5) simultaneously and partially on purchasing decisions of sasirangan cloth in the Municipality of Banjarmasin. The research was conducted using the Analysis Method i.e. Statistical Descriptive Analysis Methods used to generatean overview of the data that has been collected; Multiple Regression Analysis used to find the influence of the independent variable (X) on the dependent variable (Y) either simultaneously or partially; and Classical Assumption Test by using Ordinary Least Square (OLS) in order to get unbiased and efficient estimation values from multiple linear regression equation. The hypothesis testing was conducted by using the F test to examine the simultaneous effect of independent variable on dependent variable. The hypothesis testing was also done by using the T test to determine the effect of each independent variable on the dependent variable. The research results showed that the culture and perception factors were variables that significantly influenced the purchase decision of Sasirangan cloth in the Municipality of Banjarmasin